Awareness, Authenticity, Authority - Bandler, John (Bandler Corporation, 2017)
This presentation covers a wide range of topics relevant to making pitches to prospective donors to academia. I elaborate on effective presentations and pitches: embracing your prospect’s needs, gaining trust, being authentic, managing subtext, being cognizant of ethics, recognizing fear, admitting setbacks, navigating pitfalls, enhancing authority and engagement, and more.
Slides by John Bandler for a presentation invited by Paul Grossman, Director of Advancement, McMaster University, for his staff and colleagues at the McMaster University Major and Planned Giving Retreat, August, 2017.
Keywords: awareness; authenticity; authority; pitching; presenting; first impressions; vulnerability; ethics; failure; creativity; persuasion; fund-raising; subtext; performance